The lived experience of long-term psychiatric hospitalization of four women in Brazil - Pereira, MAO; Furegato, ARF; Pereira, A. (Blackwell Publishing, 2005)
PROBLEM: What is the experience from long-term psychiatric hospitalization? How can psychiatric nursing contribute to reduce the emotional suffering and the feeling of social exclusion related to this process?METHODS: This study was conducted on four women committed to long periods of psychiatric hospitalization in Brazil. Data were collected through open interviews and drawings made by the patients, and interpreted according to the theory of social representations.FINDINGS: Reports on the patients refer to a process of social exclusion, emotional suffering, and inadequate treatment in the hospital, leading to no other option but recurrent hospitalization.CONCLUSION: Negative experiences related to long-term hospitalization could possibly be minimized through adequate assistance provided by psychiatric nursing in open services, as proposed in the recent Brazilian psychiatric reform.
Keywords: Psychiatric nursing; long-term hospitalization; social representations; social exclusion; suffering